Activity and Health During the SARS-CoV2 Pandemic (ASAP): Study Protocol for a Multi-National Network Trial - Wilke, Jan; Mohr, Lisa; Tenforde, Adam S.; Vogel, Oliver; Hespanhol, Luiz; Vogt, Lutz; Verhagen, Evert; Hollander, Karsten (Frontiers in Medicine, 2020)
Introduction: The worldwide spread of the novel coronavirus (SARS-CoV2) has prompted numerous countries to restrict public life. Related measures, such as limits on social gatherings, business closures or lockdowns, are expected to considerably reduce the individual opportunities to move outside the home. As physical activity (PA) and sport participation significantly contribute to health, this study has two objectives. The first aim is to assess changes in PA and well-being since the coronavirus outbreak in affected countries. The second aim is to evaluate the impact of digital home-based exercise programs on PA as well as physical and mental health outcomes. Method: A multinational network trial will be conducted with three planned phases. In study part A, a structured survey will be administered. It investigates changes in PA levels and health during the coronavirus outbreak and measures the preferences of the participants regarding online training programs. Part B, is a two-armed, randomized-controlled trial. Participants assigned to the intervention group will complete a digital 4-week home exercise training (live streaming via internet) with contents guided by the survey results. The control group (CG) will not receive the program. Subsequently, in study part C, the members of both groups will have 4-week access to a digital archive of pre-recorded workouts. Similar to the initial survey, questionnaires will be used in the intervention trials in order to estimate the exercise effects on markers of mental and physical health. Discussion: Our findings will provide valuable insights into the influences of governmental restrictions on PA levels and well-being during a global pandemic. We, furthermore, provide the first evaluation of an intervention aiming to tackle potential health problems arising from such situation. Results of the study may guide policy makers on methods to maintain PA and health when restricting public life.